2016
DOI: 10.1016/j.immuni.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bladder Epithelium Induced by Cytolytic Mast Cell Granules

Abstract: Summary Programmed death and shedding of epithelial cells is a powerful defense mechanism to reduce bacterial burden during infection but this activity cannot be indiscriminate because of the critical barrier function of the epithelium. We report that during cystitis, shedding of infected bladder epithelial cells (BECs) was preceded by the recruitment of mast cells (MCs) directly underneath the superficial epithelium where they docked and extruded their granules. MCs were responding to interleukin-1β (IL-1β) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 35 publications
5
66
0
1
Order By: Relevance
“…However, during infections with helminth parasites, connective tissue mast cells migrate closer to the mucosal surfaces and may change their protease expression [57,59]. In addition, a recent study showed that activated urine bladder mast cells released granules containing chymase/mMCP-4, inducing apoptosis and shedding of the epithelial umbrella cells, to remove the infection with uropathogenic E. coli [60]. Furthermore, in the intestine mMCP-4 contributes to homeostatic epithelial cell migration and barrier function [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, during infections with helminth parasites, connective tissue mast cells migrate closer to the mucosal surfaces and may change their protease expression [57,59]. In addition, a recent study showed that activated urine bladder mast cells released granules containing chymase/mMCP-4, inducing apoptosis and shedding of the epithelial umbrella cells, to remove the infection with uropathogenic E. coli [60]. Furthermore, in the intestine mMCP-4 contributes to homeostatic epithelial cell migration and barrier function [34].…”
Section: Discussionmentioning
confidence: 99%
“…These studies were performed using Mcpt4 −/− mice, which do not exhibit any marked defect in the expression of proteases with trypsin‐like or CPA activity, for example, MCPT6 or CPA3, respectively . In the first study, Choi et al investigated how mast cells contribute to protection against urinary tract infections (UTIs) caused by uropathogenic E. coli . Uropathogenic E. coli gain access to the bladder and rapidly invade superficial bladder epithelial cells to avoid being flushed out when urine is voided.…”
Section: Mast Cells and Bacterial Infectionsmentioning
confidence: 99%
“…These studies were performed using Mcpt4 −/− mice, which do not exhibit any marked defect in the expression of proteases with trypsinlike or CPA activity, for example, MCPT6 or CPA3, respectively. 42 In the first study, Choi et al 60 The second study was performed by our own group. By using mice with c-KIT-independent mast cell deficiency, we showed that mast cells are required for an effective immune response during systemic GBS infections.…”
Section: Protective Effects Of Mast Cell-restricted Proteasesmentioning
confidence: 99%
“…will be important to identify potential downstream targets aimed at suppressing MC degranulation and disease. Alternatively, knowledge of how CRF 1 enhances MC function could also be applied to situations in which augmenting MC responses would be beneficial to the host, such as for the clearance of pathogens [70,71] or as vaccine adjuvants [72,73].…”
Section: Discussionmentioning
confidence: 99%